Evaluation of Remdesivir in Liver Functions Covid-19 Patients At Bhayangkara H.S Samsoeri Mertojoso Hospital Surabaya - Maria Angelia Yoshida; Didik Hasmono; Ruddy Hartono; Mohammad Subkhan (Jurnal Sains dan Kesehatan, 2022)
Remdesivir is one of the effective anti-viral drugs used as a Covid-19 therapy at moderate, severe and critical degrees. Side effects that need to be considered in the use of remdesivir is hepatotoxicity. The active metabolite of remdesivir (GS-44152) is thought to play a role in mitochondrial damage in liver cells, inhibiting bile acid transport, and inducing oxidative stress. This study was conducted to evaluate the use of remdesivir associated with changes in liver function SGOT and SGPT. This study was retrospective observation of moderate, severe and critical COVID-19 patients receiving remdesivir with inclusion criteria of all inpatient medical records at Bhayangkara Hospital Surabaya for the period of August 2020-July 2021. The results showed that significant increase of liver enzymes occurred in SGPT (Pre 29 .50; Post 33.50) while in SGOT (Pre 33.00; Post 26.00), enzymes were significantly decreased. The decrease was greater in the SGPT (Pre 69.00; Post 47.00) and SGOT (Pre 56.00; Post 32.00) hepatoprotector groups. The use of remdesivir had no effect on liver function as indicated by an increase in SGPT value and a decrease in SGOT value, both of which were still in the normal range.